Skin and Systemic Inflammation in Schnitzler's Syndrome Are Associated With Neutrophil Extracellular Trap Formation - Bonnekoh, Hanna; Scheffel, Jörg; Wu, Jim; Hoffmann, Sheila; Maurer, Marcus; Krause, Karoline (Frontiers in Immunology, 2019)
Schnitzler’s syndrome is a rare autoinflammatory disorder characterized by interleukin-1ß-mediated and neutrophil-dominated inflammation. Neutrophil extracellular traps (NETs) are web-like structures of decondensed chromatin, histones and antimicrobial peptides released by neutrophils. NETs were initially described in the context of pathogen defense but are also involved in autoimmune-mediated skin diseases. Here, we assessed the role of neutrophil extracellular trap formation (NETosis) in Schnitzler’s syndrome. Immunofluorescence co-staining of myeloperoxidase and subnucleosomal complex was performed on lesional skin samples from patients with Schnitzler’s syndrome, other neutrophilic dermatoses (cryopyrin-associated periodic syndrome, Sweet syndrome and pyoderma gangrenosum), urticarial vasculitis and chronic spontaneous urticaria as well as healthy control skin. Blood neutrophils from patients with Schnitzler’s syndrome and controls were isolated, and NETosis was induced by phorbol 12-myristate 13-acetate (PMA). Also, NETosis of control neutrophils induced by symptomatic Schnitzler’s syndrome sera, cytokines and sub-threshold PMA doses was studied. Immunofluorescence co-staining revealed widespread and substantial NET formation in lesional skin of Schnitzler’s syndrome but absence of NETs in chronic spontaneous urticaria and control skin. Neutrophils undergoing NETosis were observed in the skin of other neutrophilic diseases too. Correspondingly, blood neutrophils from Schnitzler’s syndrome patients showed significantly elevated NETosis rates compared to control neutrophils following stimulation with PMA. Increased NETosis correlated well with high levels of C-reactive protein (CRP). SchS patients with the lowest NETosis rates had persistent joint and bone pain despite IL-1 blockade. Stimulation of control neutrophils and sub-threshold PMA with sera of symptomatic Schnitzler’s syndrome patients disclosed enhanced NETosis as compared to control sera. Our results suggest that the induction of NET formation by neutrophils contributes to skin and systemic inflammation and may support the resolution of local inflammation in Schnitzler’s syndrome.